2020
DOI: 10.1038/s41598-020-69673-w
|View full text |Cite
|
Sign up to set email alerts
|

Sovateltide (IRL-1620) activates neuronal differentiation and prevents mitochondrial dysfunction in adult mammalian brains following stroke

Abstract: The development of effective drugs for stroke is urgently required as it is the 2nd largest killer in the world and its incidence is likely to increase in the future. We have demonstrated cerebral endothelin B receptors (ETBR) as a potential target to treat acute cerebral ischemic stroke. However, the mechanism of ETBR mediated neural regeneration and repair remains elusive. In this study, a permanent middle cerebral artery occluded (MCAO) rat model was used. Sovateltide (an ETBR agonist) injected intravenousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 59 publications
2
28
0
Order By: Relevance
“…We assessed the mitochondrial DNA using mitochondrial DNA specific TaqMan probe and primers for MT-ATP8 gene, which is present in mitochondrial genome as a single copy and is absent in nuclear genome. We performed in situ PCR in kidney tissues and carried out fluorescence confocal microscopy to detect the FAM labeled TaqMan probe as described in our previous studies ( Ranjan et al, 2012 ; AK Ranjan and Hardikar, 2015 ; Ranjan et al, 2020 ). We observed that CQ had significantly higher mitochondrial DNA fluorescence than vehicle, which could be due to less ROS generation in CQ than vehicle ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…We assessed the mitochondrial DNA using mitochondrial DNA specific TaqMan probe and primers for MT-ATP8 gene, which is present in mitochondrial genome as a single copy and is absent in nuclear genome. We performed in situ PCR in kidney tissues and carried out fluorescence confocal microscopy to detect the FAM labeled TaqMan probe as described in our previous studies ( Ranjan et al, 2012 ; AK Ranjan and Hardikar, 2015 ; Ranjan et al, 2020 ). We observed that CQ had significantly higher mitochondrial DNA fluorescence than vehicle, which could be due to less ROS generation in CQ than vehicle ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous sovateltide resulted in higher neuronal progenitor cell (NPC) differentiation and better mitochondrial morphology and biogenesis in the brain of stroked rats [ 41 , 42 ]. Exposure of cultured NPCs to hypoxia also showed higher NPC differentiation and maturation with sovateltide [ 41 , 42 ]. ET B receptors are vital for the development of neural crest-derived epidermal melanocytes and enteric neurons [ 19 , 27 , 28 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of ET B receptors by sovateltide facilitated restoration of cerebral blood flow and improvement in neurological and motor function in a rat model of cerebral ischemia [ 24 , 25 , 29 , 30 ]. Sovateltide-treated animals showed strong evidence of neural tissue repair and regeneration, including decreased infarct volume and oxidative stress, increased pro-angiogenic, pro-survival and anti-apoptotic markers; and increased numbers of proliferating cells [ 24 , 25 , 29 , 30 , 41 , 42 ]. The SONAR trial administered a selective ET A receptor antagonist (leaving ET B receptors unblocked) in patients with type 2 diabetes mellitus with chronic kidney disease [ 51 ], who have a significantly greater risk of cardiovascular accidents [ 52 ], providing indirect supporting evidence of a reduced number of nonfatal strokes in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Sovateltide (an ET B receptor agonist) injected intravenously showed higher neuronal progenitor cells (NPCs) differentiation along with better mitochondrial morphology and biogenesis in the brain stroked rats. Exposure of cultured NPCs to hypoxia also showed higher NPC differentiation and maturation with sovateltide [46, 47]. ET B receptors are vital for the development of neural crest-derived epidermal melanocytes and enteric neurons [19, 27, 28, 48, 49].…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of ET B receptors by sovateltide facilitated restoration of cerebral blood flow and improvement in neurological and motor function after stroke [24, 25, 29, 30]. Sovateltide treated animals showed strong evidence of neural tissue repair and regeneration including decrease in infarct volume and oxidative stress, increased pro-angiogenic, pro-survival and antiapoptotic markers as well as number of proliferating cells [24, 25, 29, 30, 46, 47]. A safe and maximum tolerated dose of sovateltide was determined in the clinical phase I trial (CTRI/2016/11/007509) in healthy human volunteers [5].…”
Section: Discussionmentioning
confidence: 99%